Aplikasi Pupuk Bokashi Padat Berbahan Dasar Feses Babi dengan Level Berbeda terhadap Pertumbuhan Tanaman Sengon Laut (Paraserianthes falcataria (L.) Nielsen). - Patrisius Klau; Stefanus Sio; Polikarpia W. Bani (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2019)
Results purpose this study was to determine the effect of the application of solid bocation fertilizer made from pig feces with different levels on the growth of marine (Paraserianthes falcataria (L.) Nielsen) . Result use design (CRD) consisting of 4 treatments and 3 replications and each replication consisted of 5 so that there were 60 polybags. R0 = Without giving Bocation (control), R1 = Application of Bokashi 500 g / polybag, R2 = Application of Bocation 750 g / polybag, R3 = Application of bocation 1000 g / polybag. Observation variables namely plant height. The results this study showed that administration of solid bokashi at the level of 1000 grams / polybag significantly affected plant height of 12.43 cm, number of leaves 9.93 stems, stem diameter of 0.74 mm. Conclusion of this study is the administration of solid Bocation fertilizer made from pig feces is very effective in increasing the value of soil fertility so that it can increase the growth of marine sengon plants with increasing plant height, number of leaf stalks and stem diameter and administration of solid Bokashi fertilizer based on pig feces at the level of 1000 gr (R3) gave the best results on plant height of 12.43 cm / plant; The number of stalks was 9.93 stalks / plant and stem diameter was 0.74 cm / plant. This result is better than Bokashi 500 gr (R1), 750 gr (R2) and Control (R0) treatments.